The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1152/jappl.1997.82.1.317
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation and metabolism among rat strains

Abstract: We examined ventilation and metabolism in four rat strains with variation in traits for body weight and/or blood pressure regulation. Sprague-Dawley [SD; 8 males (M), 8 females (F)], Brown Norway (BN; 10 M, 11 F), and Zucker (Z; 11 M, 12 F) rats were compared with Koletsky (K; 11 M, 11 F) rats. With the use of noninvasive plethysmography, frequency, tidal volume, minute ventilation (VE), O2 consumption, and CO2 production were derived at rest during normoxia (room air) and during the 5th minute of exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 19 publications
(28 reference statements)
7
103
1
1
Order By: Relevance
“…Volumes ranging between 5 and 10 ml are frequently used for BAL in rats (26)(27)(28). However, these volumes are high compared to the tidal volume, which is close to 1 ml for a rat weighing 300 g (29). Therefore, in the present study the volume was limited to 1 ml in order to preserve the integrity of the pulmonary barrier as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Volumes ranging between 5 and 10 ml are frequently used for BAL in rats (26)(27)(28). However, these volumes are high compared to the tidal volume, which is close to 1 ml for a rat weighing 300 g (29). Therefore, in the present study the volume was limited to 1 ml in order to preserve the integrity of the pulmonary barrier as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the work by Strohl and collaborators (31), few studies allow direct comparisons of the hypercapnic ventilatory response between male and female rats. These authors reported no sex-related differences in ventilatory activity, but the fact that their experiments were performed under hyperoxic conditions (inspired O 2 fraction ϭ 0.93) makes it difficult to determine whether these results truly contrast with ours.…”
Section: Nms and Sex-specific Plasticity Of The Hypercapnic Ventilatomentioning
confidence: 99%
“…Weight normalized values for basal ventilation on room air were similar to prior published values for the same rat strain (Strohl et al, 1997;Mouradian et al, 2012). Also as described before, the hypoxic ventilatory reflex of intact rats consisted of a selective increase in breathing frequency (Hodges et al, 2002).…”
Section: Recovery Of Normal Ventilation and Blood Gases A Week After supporting
confidence: 83%